2006
DOI: 10.1590/s1678-58782006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Punching and broaching combos - a newstamping tool

Abstract: The crescent searches for the reduction in time production are a factor that stimulates the improvement of the existent manufacturing techniques (Von Steeg 2002 and Waurzyniak 2002). Nowadays, the new researched processes should make possible the fabrication of pieces in a smaller time with a better use of the material resources and equipments (Klein 2002). The present work has for objective to show the viability of a combined tool that makes possible to perform a punching followed by a broaching in only one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Bottom of conventional punch is shown in Fig. 1 [1]. For this purpose, it is able to modify the part of the process under conventional punching process to improve the quality of punching.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom of conventional punch is shown in Fig. 1 [1]. For this purpose, it is able to modify the part of the process under conventional punching process to improve the quality of punching.…”
Section: Introductionmentioning
confidence: 99%
“…Observing this research gap, Mello and Marcondes [11] reported a new perforating process via a punching-broaching combined tool, i.e. a tool with a punch tip and broaching teeth at its body.…”
Section: Introductionmentioning
confidence: 99%
“…In the Society of Manufacturing Engineers (SME, 1990), it is a descriptive on dies for broaching slots in a round shaft. Mello and Marcondes (2006) showed this new stamping tool of punching and broaching process composed basically by punch and die, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the traditional punch was endowed with broaching teeth. Mello and Marcondes (2006) studied some diameters of the punches and geometric form of the teeth used for broaching. In this study, several items were analyzed in order to identify the main variables and their process influences, i.e.…”
Section: Introductionmentioning
confidence: 99%